2022
DOI: 10.1039/d1fo03143k
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effect of bile salt hydrolase from aLactobacillus johnsoniistrain mediated by FXR pathway regulation

Abstract: Hypercholesterolemia is a major risk factor for cardiovascular diseases worldwide. In this study, recombinant bile salt hydrolase (BSH) from the strain L. johnsonii 334 with high cholesterol reduction ability was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Then, LP104 induced the activation of the FXR/SHP signaling pathway by increasing hepatic CA and CDCA concentration (Figure E,F), although activated FXR can upregulate SHP to inhibit BA synthesis in the liver . The L. johnsonii strain exhibited a similar regulative mechanism on FXR signal to improve HFD-induced lipid metabolism disorders, which was consistent with the effects of LP104 . These results indicated that LP104 resulted in the suppression of intestinal FXR to negative feedback regulate hepatic BA synthesis.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Then, LP104 induced the activation of the FXR/SHP signaling pathway by increasing hepatic CA and CDCA concentration (Figure E,F), although activated FXR can upregulate SHP to inhibit BA synthesis in the liver . The L. johnsonii strain exhibited a similar regulative mechanism on FXR signal to improve HFD-induced lipid metabolism disorders, which was consistent with the effects of LP104 . These results indicated that LP104 resulted in the suppression of intestinal FXR to negative feedback regulate hepatic BA synthesis.…”
Section: Discussionsupporting
confidence: 72%
“…As shown in Figure C, the present data further demonstrated that HFD could facilitate the excretions of CDCA, α-MCA, β-MCA, DCA, and LCA with feces relative to the Con group, but the fecal concentration of unconjugated BAs was higher in the LP104 group than the HFD group as a result of the increased levels of CA, CDCA, and β-MCA after LP104 treatment (Figure A,C). Some probiotics such as L. paracasei FZU103 and L. johnsonii 334 promote the hepatic BA biosynthesis accompanied by enlarged fecal BA loss, which exhibit similar effects as LP104 administration. , In addition, serum BAs mainly come from the reabsorption of BAs in the portal or hepatic vein . The metabolic changes of BAs in the serum and liver were basically consistent after LP104 treatment for 8 weeks (Figures D and D).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…lactis F1-7 can improve hyperlipidemia by inhibiting the FXR/ FGF15 pathway. [42][43][44] The credibility of the experimental results was affected by this evidence. Finally, the number of animals used in the present study was relatively small.…”
Section: Discussionmentioning
confidence: 99%